Media interventions in public space: A place-based approach for the assessment of human experience in digitally augmented urban environments - Pavlaki, Evangelia (2021)
Considering the amount of time people spend occupying public spaces during their lives in the city, the quality of the urban environment is crucial as it is found to have significant effects on their behaviour, performance, social development as well as their wellbeing (Adams, 2014; Thwaites et al., 2017; Anderson et al., 2017). The last decade, urban public spaces have changed considerably through the gradual integration of digital technology into them. Furthermore, urban architecture and public art have manifested possibilities they never had before. The result is that contemporary public spaces are now highly digitized. This combination of physical and digital elements in space, also known as media architecture and urban media art, is frequently thought as a tool to stimulate and amplify casual urban experiences. While most research studies on urban situated digital technologies focus either on their functional- technical dimension or on their social effects, little is known on the overall impact of these media stimuli on the versatile aspects of human experience. In this context, the study by adopting a place-based approach, aims to interpret how the multiple interrelated elements of human experience can be affected by the implementation of digital installations and, ultimately, explore the potential of digital augmented public spaces to act as mediators for more responsive and citizen-centred urban environments. The theoretical framework of the study is based on fundamental Place theories which have been assessed and synthesized in order to develop a new comprehensive basis for the concept of place experience. The research project employed a pragmatic methodology to human- environment interaction which links the academic fields of urban and landscape design, phenomenology, psychology, environmental psychology and neuroscience using an embedded case study approach. It triangulated several techniques which include field observations, on-site discussions, semi-structured and in-depth phenomenological interviews, a field-based psychophysiological experiment as well as digital ethnography. The research found critical transformations in place experience during the digital augmentation of the four examined public spaces which involved changes in space’s activity, vibrancy, social interaction and level of contact with strangers, inclusion, human proxemics as well as emergence of playful behaviour, phenomena of place personalization and creative bodily expression. The main contribution of the study is threefold; a. it provides theoretical input through the examination of the affordances of urban media interventions in place experience and of their value as placemaking tools; b. it delivers methodological input through the development of a multidisciplinary pragmatic framework for the assessment and evaluation of complex phenomena associated with human experience in public space; c. it offers empirical input through the suggestion of a number of design and planning considerations for the development of active, pleasant and human-friendly urban media environments.